The Essential Handbook of General Surgery - Saad Muhmood Hussain Arraki; Tharveen Nair Chandrasekran; Bhuwaneswaran Vijayam (Penerbit UTHM, 2026)
Written by surgeons, clinical educators and medical students across stages of training, this surgical reference text combines clinical expertise with the student perspective and delivers complex surgical principles in accessible, substantial detail. Contributors have worked together to create a resource that addresses both theoretical foundations and practical application. Full-colour illustrations and structured explanations guide readers through core surgical concepts, procedures and clinical reasoning. Each chapter builds understanding systematically, with visual aids that clarify anatomy, technique and decision-making. Medical students can use it to prepare for exams, enter surgical rotations or build foundational knowledge for practice. House officers and medical officers will find it equally valuable as they develop clinical skills and surgical judgment. Beyond a reference textbook, it represents genuine collaboration within the surgical education community and serves as a reliable companion for both learning and teaching surgery. Its clear presentation and comprehensive coverage make it suitable for individual study, small group teaching, and bedside reference.